THE INFLUENCE OF PROJECT BASED LEARNING IMPLEMENTATION ON STUDENTS’ ENGLISH LEARNING MOTIVATION AT SMK PEMBANGUNAN BAGAN BATU - Nahri, Putri Rizki Afdhal; Fauzana, Riri (State Islamic University of Sultan Syarif Kasim Riau, 2025)
This research focused on the influence of Project-Based Learning (PBL) implementation on student English learning motivation at Vocational High School. This research aimed at finding out whether the implementation of PBL significantly contributed to increase student English learning motivation. This research was conducted to the eleventh-grade students at Vocational High School in Bagan Batu. Quantitative approach was used in this research with correlational design. Data were collected through two instruments observation sheet to measure PBL implementation and questionnaire to assess student English learning motivation. Data were analyzed by using descriptive statistics, Shapiro-Wilk normality test, and Pearson Product-Moment correlation analysis with SPSS 25. The research findings showed that Null hypothesis (H0) was accepted, and Alternative hypothesis (Ha) was rejected. Thus, it could be concluded that there was no significant contribution between PBL implementation and student English learning motivation. However, PBL implementation still positively influenced student engagement and enthusiasm in English learning.